Immigration and the Reallocation of Work Health Risks - Osea Giuntella; Fabrizio Mazzonna; Catia Nicodemo; Carlos Vargas-Silva (Institute for the Study of Labor (IZA), 2016)
This paper studies the effects of immigration on the allocation of occupational physical burden and work health risks. Using data for England and Wales from the Labour Force Survey, we find that, on average, immigration leads to a reallocation of UK-born workers towards jobs characterized by lower physical intensity and injury risk. The results also show important differences across skill groups. Immigration reduces the average physical burden of UK-born workers with medium levels of education, but has no significant effect on those with low levels.
Keywords: J61; I10; 330; immigration; labor-market; physical burden; work-related injuries; health